2023
DOI: 10.1002/jmri.28737
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence Applications in Glioma With 1p/19q Co‐Deletion: A Systematic Review

Abstract: As an important genomic marker for oligodendrogliomas, early determination of 1p/19q co‐deletion status is critical for guiding therapy and predicting prognosis in patients with glioma. The purpose of this study is to systematically review the literature concerning the magnetic resonance imaging (MRI) with artificial intelligence (AI) methods for predicting 1p/19q co‐deletion status in glioma. PubMed, Scopus, Embase, and IEEE Xplore were searched in accordance with the Preferred Reporting Items for systematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…By studying molecular markers in glioma tissues, we can better understand the mechanisms of tumor development, prognosis assessment, and the formulation of personalized treatment plans. Current research has identified therapeutic methods such as TERT (telomerase reverse transcriptase) promoter mutations [23][24][25], IDH1/2 (isocitrate dehydrogenase 1) mutations, and 1p/19q co-deletion [26,27]; corresponding treatments have been applied in clinical practice. Despite achieving a series of treatment outcomes, the prognosis remains poor.…”
Section: Discussionmentioning
confidence: 99%
“…By studying molecular markers in glioma tissues, we can better understand the mechanisms of tumor development, prognosis assessment, and the formulation of personalized treatment plans. Current research has identified therapeutic methods such as TERT (telomerase reverse transcriptase) promoter mutations [23][24][25], IDH1/2 (isocitrate dehydrogenase 1) mutations, and 1p/19q co-deletion [26,27]; corresponding treatments have been applied in clinical practice. Despite achieving a series of treatment outcomes, the prognosis remains poor.…”
Section: Discussionmentioning
confidence: 99%